2018
DOI: 10.1111/jebm.12323
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation following heart transplantation: A systematic review and meta‐analysis of observational studies

Abstract: Objective: Previous studies have suggested a high incidence of atrial fibrillation (AF) in heart transplant recipients. However, incidence trends of AF in heart transplant recipients remain unclear. The study's aims were (1) to investigate the pooled incidence/incidence trends of AF following heart transplantation and (2) to assess the mortality risk of heart transplant recipients with AF. Methods:A literature search for studies that reported the incidence of AF following heart transplantation was conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 57 publications
(111 reference statements)
2
26
0
Order By: Relevance
“…Vaseghi et al [21] suggested a potential involvement of parasympathetic re-innervation, but without reporting an objective demonstration, while a recent case report described PVs reconnection several years after OHT as a cause of atrial tachyarrhythmia [31] . As previously described [8] , [16] , [21] , [22] , we observed a significantly higher mortality in patients with AF episodes, confirmed by Kaplan Meyer and Cox regression analysis. It is known that an old age recipient with rejection episodes has higher mortality, but if the patient experienced AF episodes, its outcome gets worse.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Vaseghi et al [21] suggested a potential involvement of parasympathetic re-innervation, but without reporting an objective demonstration, while a recent case report described PVs reconnection several years after OHT as a cause of atrial tachyarrhythmia [31] . As previously described [8] , [16] , [21] , [22] , we observed a significantly higher mortality in patients with AF episodes, confirmed by Kaplan Meyer and Cox regression analysis. It is known that an old age recipient with rejection episodes has higher mortality, but if the patient experienced AF episodes, its outcome gets worse.…”
Section: Discussionsupporting
confidence: 89%
“…The reported rate of AF in the transplanted heart ranges between 0.3% [15] and 24% [16] and this variation might be due to the methods used for arrhythmia detection. In a recent review, the overall estimated rate was 10% [8] . In this study, the total rate was 23.4%, similar to the results reported by Pavri et al [16] with a comparable cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lushaj and colleagues 5 found no difference between patients with (6.5%) or without (7.1%, P = 0.76) amiodarone before HTX regarding post‐transplant AF, which could be a result of their lower overall incidence of post‐transplant AF (6.8%). A recent Cochrane meta‐analysis 47 reported a higher overall incidence of AF after HTX of 10.1%, which is in line with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Systematic reviews/meta-analyses use systematic methods to collect secondary data, critically appraise research studies, and synthesize studies [ 11 , 21 27 ]. They are designed to provide a complete, exhaustive summary of current evidence relevant to a research question and are the key to the practice of evidence-based medicine and have always been used in practice guideline [ 28 30 ]. Assessment of quality and quantity of diabetic systematic reviews/meta-analyses by bibliometrics analysis should be very important for diabetic research.…”
Section: Introductionmentioning
confidence: 99%